Soils at archaeological monuments of the Bronze Age – A key to the Holocene landscape dynamics in the broadleaf forest area of the Russian Plain. (20th July 2021) - Makeev, Alexander; Rusakov, Alexey; Kurbanova, Fatima; Khokhlova, Olga; Kust, Pavel; Lebedeva, Marina; Milanovskiy, Evgeniy; Egli, Markus; Denisova, Elizaveta; Aseyeva, Elena; Rusakova, Elena; Mihailov, Evgeniy
Abstract: During the second half of the Holocene, the Russian Plain experienced several climatic oscillations giving rise to changing vegetation patterns. The spatial variability of vegetation changes and its effects on soils is still a matter of debate. In the present study landscape response to Holocene climatic cycles was analysed on the base of detailed morphological, chemical and microbiomorphic analyses of a paleosol buried under the kurgan of the Abashevo culture (Middle Bronze Age) and a surface soil. Both soils located at the Tokhmeyevo kurgan cemetery (the Middle Volga region, Chuvash Republic, Russia) developed from the same parent material (mantle loam), at the same elevation and in close proximity to each other. Both soils, classified as Retisols, show a similar morphology and key analytical features indicating similar environment. The pollen and phytolith spectra confirm that both buried and surface soils formed under similar forest vegetation. The buried and surface soils at the Tokhmeyevo cemetery could be compared with the previously studied soils of the Sareevo settlement of the Early Iron Age and the Taushkasy kurgan cemetery of the Bronze Age. These studies confirm the stability of the forest environment at the southern boundary of the forest belt since the Bronze Age. At the same time, the buried soil at the Tokhmeyevo cemetery has a thick mollic horizon and black organic coatings overlaying brown clay cutans in the argic horizons, which sets it apart from the surface soil. The radiocarbon dates for the humus in the mollic horizon and black coatings in the argic horizon are surprisingly close to each other (about 5.5 cal ka BP and 5.2 cal ka BP, respectively). The data indicate that the black cutans are derived from degradation of the mollic horizon caused by a sudden increase in humidity during the episodes of extreme summer rainfall events. Our study also prove that the Abashevo people had complicated burial funeral rites. The earth mounds are made of the upper horizons of soils cut off from the surface in the vicinity. The central part of the mound consists of soil bricks with albic material used for the interior, while artificially rumpled material of the argic horizon was used for coverage. The use of albic and artificially rumpled material of argic horizon for earth mound construction implies the similarity between the buried and surface soils since the Bronze Age until today. Thus, the study of such construction techniques is important both for archaeology and paleogeography (paleopedology).